Strength training for children and adolescents - Faigenbaum, A. D. (Strength and conditioning: biological principles and practical applications, 2011)
Despite outdated concerns regarding the safety and effectiveness of youth strength training, a compelling body of scientific evidence now indicates that strength training has the potential to offer observable health and fitness value to children and adolescents provided that appropriate training guidelines are followed and qualified instruction is available. In addition to fitness-related benefits, the effects of strength training on selected health-related measures, including bone health, body composition, and sports-injury reduction, should be recognized by teachers, coaches, and health-care providers. If youth strength-training programmes are well designed and sensibly progressed over time, children and adolescents can gain the knowledge, skills, and self-motivation to regularly strength-train as a lifestyle choice. An important future research goal should be to establish the combination of programme variables that enhance long-term training adaptations in young athletes and youths with various medical conditions.